Contact Analysis of Gear and Rack under the Action of Friction - Li Quancai; 2Xiao Weizhong; Liu Zhongming (Jixie chuandong)
In the case of dry friction,the stress value and distribution on and under contact surface of gear and rack are analyzed in terms of elasticity theory,the results show that the maximum shear stress moves to the tooth surface with the increase of friction factor,and the maximum shear stress mostly occurs on the nether boundary point of single tooth mesh area of the gear.